Architecture of the HIV-1 glycan shield - Pritchard, L (2014)
In recent years the glycan shield of the HIV-1 envelope spike (Env) has emerged as a potential target for microbicide and vaccine design. The densely packed glycans on its surface include an intrinsic population of under-processed oligomannose structures, and a number of lectins and broadly neutralising antibodies (bnAbs) have been isolated which are reactive to these ‘non-self’ glycan structures. The potential value of these agents in therapeutic or vaccine contexts depends upon the prevalence of their glycan targets in nature and their resilience to sequence mutation. Here the prevalence of oligomannose-type glycans on recombinant gp120 was demonstrated across a panel of isolates, revealing subtle cross clade differences. Alanine scanning of all potential N-glycosylation sites (PNGSs) within a model gp120 demonstrated the overall stability of the oligomannose population, but highlighted regions of glycan clusters where individual glycans act to limit the processing of their neighbours. This was formally demonstrated for the N332 ‘site of vulnerability’, where deletion of nearby glycosylation sites led to altered glycan processing at the N332 site. A panel of N332-dependent bnAbs was screened for their ability to tolerate such changes in glycan processing, with differing results. While some displayed promiscuous binding, others were more sensitive to glycan microheterogeneity. Site-specific glycosylation analysis of the PGT135 epitope revealed that an intolerance of certain glycoforms may explain its limited breadth. While a greater understanding of Env glycan microheterogeneity and bnAb promiscuity is required, these findings reveal insights into the architecture of the HIV-1 glycan shield that suggest it is a conserved and robust target for drug and vaccine design.